2008
DOI: 10.1117/12.786019
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of flexible oil lines using FBG sensors

Abstract: Thorough the last two decades, oil and gas reservoirs discovered and developed in deep and ultra deep waters have continuously posed challenges to petroleum exploration and production activities in offshore basins. Maintaining optimum flow rates of oil and gas from subsea wellheads to surface processing facilities demands new technological solutions for petroleum companies operating in such frontiers. Integrity assurance of structures, equipment, and flow lines plays a major role in maximizing offshore product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 2 publications
0
4
0
3
Order By: Relevance
“…Fiber-optics Bragg grating (FBG) sensors technology has also been used to monitor flexible riser. In [21] two methodologies to monitor strain in flexible risers are developed. In the first approach, permanent FBG strain gages were installed on all wires of the armor layer.…”
Section: Flexible Riser Inspection and Monitoringmentioning
confidence: 99%
“…Fiber-optics Bragg grating (FBG) sensors technology has also been used to monitor flexible riser. In [21] two methodologies to monitor strain in flexible risers are developed. In the first approach, permanent FBG strain gages were installed on all wires of the armor layer.…”
Section: Flexible Riser Inspection and Monitoringmentioning
confidence: 99%
“…From 2002 to 2010, many researchers found that the FBG sensors on flexible pipelines or risers can be used to monitor their fracture failure or vortex-induced vibration and the results are turned out to be satisfying [10][11][12] . In 2004, D. Brower applied optical fiber sensors in structural performance tests in deepwater oil fields 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Nesta seção serão apresentados alguns projetos de pesquisa alinhados com o monitoramento e inspeção dos risers. [14,35]. Ao ocorrer o rompimento de um ou mais arames, deformações circunferenciais, longitudinais e torsionais são transmitidas para a capa do riser, que passa a exibir deformações dinâmicas com uma assinatura diferente da inicial.…”
Section: Outras Técnicas Para Monitoramento De Risersunclassified